2020
DOI: 10.1021/acsnano.0c01957
|View full text |Cite
|
Sign up to set email alerts
|

Universal Interfacial Control through Polymeric Nanomosaic Coating for Block Copolymer Nanopatterning

Abstract: The employment of self-assembly of soft materials has been accepted as an inexpensive, robust, and reliable patterning method. As their self-assembly relies on the delicate molecular interactions near the substrate, a precise prediction/control of the interface structure and dynamics is critical to achieve desired nanostructures. Herein, a polymeric nanomosaic (PNM) pattern is created from the air/water interfacial self-assembly of a block copolymer (BCP) and introduced as an effective interfacial energy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…This anisotropic roughness-induced alignment of BCP nanopatterns can be rationalized with a description of the system free energy. 18 The self-assembly of BCP thin films is sensitive to the interfacial conditions such as the BCP− substrate interface interactions 25,26 and a substrate roughness 27 in this study. The microphase separation of BCPs generally occurs toward the minimization of interface energy between BCP domains, 28 while the roughness of substrates increases the domain interfaces in BCP thin films.…”
Section: T H Imentioning
confidence: 75%
“…This anisotropic roughness-induced alignment of BCP nanopatterns can be rationalized with a description of the system free energy. 18 The self-assembly of BCP thin films is sensitive to the interfacial conditions such as the BCP− substrate interface interactions 25,26 and a substrate roughness 27 in this study. The microphase separation of BCPs generally occurs toward the minimization of interface energy between BCP domains, 28 while the roughness of substrates increases the domain interfaces in BCP thin films.…”
Section: T H Imentioning
confidence: 75%
“…The three different PS- b -PMMA block-copolymers have similar material properties, except for their wetting behavior due to different block lengths. 29 , 30 PMMA is relatively more hydrophilic, than PS and it has been shown that PS-PMMA copolymers become more hydrophobic with increasing PS contents. 31 PS- b -PMMA films are well known to form self-assembled nanostructures of PS and PMMA domains upon heating, such as islands or lamellas.…”
Section: Resultsmentioning
confidence: 99%
“… 31 PS- b -PMMA films are well known to form self-assembled nanostructures of PS and PMMA domains upon heating, such as islands or lamellas. Depending on the length of the polymer blocks, they can form lamellar nanostructures of different sizes, for example, ∼10 nm lamella spacing for PS- b -PMMA 25–26 k and ∼50 nm lamella spacing for PS- b -PMMA 52–52 k. 30 While two of our block copolymers (21 k:21 k and 52 k:52 k) have a similar PS/PMMA ratio, the different nanostructures will influence the wettability properties of the copolymers. The larger PMMA domains in PS- b -PMMA 52 k:52 k should cause a higher polarity than that in PS- b -PMMA 21 k:21 k, whereas PS- b -PMMA 20 k:50 k should be the most polar copolymer.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 Besides, a self-assembled BCP film located on top of an underlying high-χ BCP layer can also provide an efficient orientational control of high-χ BCP domains when the surface energies between the two layers are carefully matched. 19,20 Nevertheless, this latter concept was demonstrated only for fully organic high-χ BCPs with large periods, although smart layering processes were employed to achieve perpendicular features. It is noteworthy that early attempts to pattern BCP layers self-assembled onto chemical templates through a poly(methyl methacrylate) top coat were pursued by Yoshida et al 21 However, in this particular study, the e-beam lithographic step is rather employed to remove the TC layer instead of an actual patterning.…”
Section: Introductionmentioning
confidence: 99%